Efficacy of Systemic Treatments of Nail Psoriasis: A Systemic Literature Review and Meta-Analysis - Zhang, Xuan; Xie, Bingbing; He, Yanling (Frontiers in Medicine, 2021)
Abstract IMPORTANCE: Nail involvement is a common condition in patients with psoriasis. The treatment of nail psoriasis is considered challenging and is often left untreated by physicians. OBJECTIVE: To assess the efficacy of current systemic treatments on nail psoriasis. DATA SOURCES: PubMed, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for relevant articles from inception to September 1, 2020. Included articles were restricted to English language and human studies. STUDY SELECTION: This was a systematic literature review with meta-analysis. Thirty-five random control trials that evaluated systemic therapies for nail psoriasis were selected in the systemic review. Among them, we retained 14 trials for meta-analysis. DATA EXTRACTION AND SYNTHESIS: This study was conducted in accordance with the preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) 2015 statement. All steps were performed by two independent investigators, and any disagreements were resolved by a third investigator. Meta-analysis of aggregated study data was conducted to assess therapeutic efficacy. The use of random-effects model was based on high heterogeneity as a variable endpoint in different studies. MAIN OUTCOMES AND MEASURES: Therapeutic effects on nail psoriasis were expressed in terms of effect sizes with 95% CIs. RESULTS: We included 35 random control trials (RCTs) in this systemic review. At baseline, a high prevalence (62.1%) of nail psoriasis was confirmed. The meta-analysis included 14 trials highlighting that biologic and small-molecule therapies were effective in treating nail psoriasis with variable effect size magnitudes [-0.89 (-1.10, -0.68), I2 =84%]. In particular, tofacitinib and ixekizumab showed the most significant scale of effect size magnitudes in treating nail psoriasis (-1.08 points and -0.93 points, respectively). We also found that a higher dose of tofacitinib and ixekizumab had similar effectiveness, and anti-IL-17 agents seem to be superior in effectiveness compared to anti-TNF-α therapies in the treatment of nail psoriasis. However, these results must be displayed carefully as variable endpoints in different studies. CONCLUSIONS AND RELEVANCE: This study provides a comprehensive overview of systemic treatments for nail psoriasis. Priority should be given to administering biologic and small-molecule therapies to patients with psoriatic nail damage.